PENERAPAN TEKNIK MENULIS DI SINI DAN SAAT INI (WRITING IN HERE AND NOW) DALAM PEMBELAJARAN MENULIS CERPEN - Ayu Rinjani, Graditya (2014)
This research is motivated by the implementation of learning to write short stories are intrinsically expressive, but implemented are less productive and actually become an own difficulties for students. Students difficulties in presenting ideas or ideas they have in mind into a post. This paper is intent to examine how the ability of eighth grade students of SMP Negeri 15 Bandung in writing short stories before and after participating in learning the use Technical Writing in Here and Now in the experimental class, how the ability of eighth grade students of SMP Negeri 15 Bandung in writing short stories before and after participating in learning who do not use Technical Writing in Here and Now in control class and is there a significant difference in the ability to write short stories eighth grade students of SMP Negeri 15 Bandung between the experimental class and the control class. The objectives are to understand determine the ability of eighth grade students of SMP Negeri 15 Bandung in writing short stories before and after participating in learning the use Technical Writing in Here and Now in the experimental class, determine the ability of eighth grade students of SMP Negeri 15 Bandung in writing short stories before and after participating in learning that do not use Technical Writing in Here and Now in control class, and describe there is or is not a significant difference in the ability to write short stories eighth grade students of SMP Negeri 15 Bandung between the experimental class and the control class. The method used in this study is quasi-experimental methods, the research design is control group design. The data in this study obtained are the test result of writing short stories after pre-test and post-test in the experimental class and the control class. Data processing technique used is using a software program SPSS 20.0 for windows. In the end, the result in this study is explanations that learning experiments provide a positive influence on mastery learning to write short stories. This is evidenced by the t-test results of the average gain of the experimental group ((0.50) with an average